Psikoedukasi Pola Pengasuhan pada Perkembangan Anak - Nur Zuhriya Djuhaepa; Nurul Ain; Qhanita Ghanaya Has; Sindi Agustina; Ahmad Ridfah; Ismalandari Ismail (CV. Multi Kreasi Media, 2022)
Abstract. Psychoeducation is carried out to provide information to parents or who will become parents about types of parenting and also their effects on child development. The topic of psychoeducation is about what types of parenting styles are and the effects of each type of parenting on children's development. Psychoeducation was carried out by distributing opinion columns about the effects of parenting on social media (Instagram) and distributing posters directly to parents at the Kampili Health Center, Gowa. The result of implementing this psychoeducation is that respondents understand the content and intent of the posters distributed, respondents also benefit from the information and will apply the information in their daily lives as parenting styles for their children. Key Word: Psychoeducation, Parenting Style, Child Development